Atrioventricular Valve Regurgitation in the Fetus With Atrioventricular Canal Defect: Transition From Prenatal to Postnatal Life - Davey, Brooke (Pediatr Cardiol, 2013)
Atrioventricular valve regurgitation (AVVR) is a clinically important element of the common atrioventricular canal defect. Cardiac preload and afterload increase from prenatal to postnatal life. These hemodynamic changes may increase the degree of regurgitation and affect management and prognosis. We sought to investigate the frequency of change in degree of AVVR from fetal to postnatal life in this patient population. Subjects who underwent both fetal and postnatal echocardiography within 4 weeks of life between January 2008 and September 2010 were included in the study. Degree of AVVR was assessed by color Doppler imaging and scored as 0 (no regurgitation), 1 (hemodynamically insignificant regurgitation), and 2 (hemodynamically important regurgitation). Forty-nine subjects were included. Mean gestational age at fetal echocardiogram was 34 ± 2.8 weeks; age at postnatal echocardiogram was a median of <24 h of age (range 0–24). After birth, 69 % subjects had no change, 8 % of subjects had a decrease, and 22 % subjects had an increase in AVVR grade. Five patients progressed from a fetal score 0 or 1 to postnatal score 2. Neither trisomy 21 nor heterotaxy syndrome were risk factors for progression of AVVR. In patients with AV canal defects, 90 % demonstrate no hemodynamically significant change in AVVR from fetal to postnatal life, whereas 10 % display a hemodynamically significant change. AVVR appreciated in utero is predictive of neonatal regurgitation in the majority of patients. These findings have implications for the counseling and management of the fetus with AV canal defect.